Hubungan Aktivitas Fisik Dengan Kadar Asam Urat Pada Lansia di Wilayah Kerja Panti Jompo Yayasan Al-Kautsar Palu - Ali, Moh. Ilham Fikrianto; Rammang, Sisilia; Irnawan, Sri Marnianti (Universitas Pahlawan Tuanku Tambusai, 2024)
Uric acid levels are determined from the results of venous blood examination and it is categorized with normal values for men about 3.4-7.0 mg/dl and for women about 2.4-6.0 mg/dl. If food that contains high purines is consumed too much, it could lead the excessive uric acid levels in the body. Physical activity is each body movement that can increase the energy needed. The aim of the research is to determine the correlation between physical activity and uric acid levels of the elderly in Panti Jompo, Yayasan Alkautsar, Palu. This is quantitative research with an analytic descriptive approach using a cross-sectional design. The total sample was 36 elderly that taken by using a purposive sampling technique. Data collection using questionnaires and uric acid test tools. The results by using the chi-square test, obtained a p-value = 0.000 (p = <0.05). This research could conclude that there is a significant correlation between physical activity and uric acid levels of the elderly in Panti Jompo Yayasan Al-Kautsar, Palu. The elderly In Panti Jompo Yayasan Al-Kautsar, Palu should routinely examine and perform a healthy lifestyle such as doing physical activity to maintain uric acid a normal levels.